PENERAPAN TOPSIS DALAM EVALUASI KINERJA GUNA PENENTUAN BONUS PEGAWAI NON - ASN PADA KUA SIMPANG EMPAT - Anggi Anggraini; Muhammad Ardiansyah Sembiring; Santoso (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Optimal public services at the Office of Religious Affairs (KUA) are highly dependent on fair performance evaluations, including those of non-civil servant employees. Currently, the performance appraisal system at the KUA Simpang Empat is still subjective and unstandardized, which has the potential to cause unfairness in the distribution of bonuses. This study aims to develop a decision support system using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to evaluate the performance of non-ASN employees objectively, measurably, and transparently. The research was conducted using a qualitative approach through observation and interviews, followed by the design and implementation of a web-based system. Performance evaluation is based on five main criteria: overtime hours, attendance, timeliness of task completion, teamwork, and initiative and creativity, with a sample size of 10 non-ASN employees evaluated. The results of the study indicate that the developed system is capable of providing a fairer evaluation, aiding data-driven decision-making, and minimizing subjectivity in bonus distribution.